2023
DOI: 10.3390/en16135178
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Vehicle Charging Load Mobility Analysis Based on a Spatial–Temporal Method in Urban Electrified-Transportation Networks

Abstract: Charging load mobility evaluation becomes one of the main concerns for charging services and power system stability due to the stochastic nature of electrical vehicles (EVs) and is critical for the robust scheduling of economic operations at different intervals. Therefore, the EV spatial–temporal approach for load mobility forecasting is presented in this article. Furthermore, the reliability indicators of large-scale EV distribution network penetration are analyzed. The Markov decision process (MDP) theory an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…The allocation and planning of urban basic charging service facilities present a comprehensive challenge, involving multi-source data and complex scenarios. With the growing adoption of deep learning (DL) methods, research findings in time series forecasting have found extensive applications across diverse domains, including demand forecasting [43], stock trend forecasting in financial markets [44], power load forecasting [45], traffic flow forecasting [46], energy consumption forecasting [47], and more. Statistical-based time series prediction methods are commonly employed for linear time series modeling; however, real-world research reveals nonlinear characteristics within these time series.…”
Section: Introductionmentioning
confidence: 99%
“…The allocation and planning of urban basic charging service facilities present a comprehensive challenge, involving multi-source data and complex scenarios. With the growing adoption of deep learning (DL) methods, research findings in time series forecasting have found extensive applications across diverse domains, including demand forecasting [43], stock trend forecasting in financial markets [44], power load forecasting [45], traffic flow forecasting [46], energy consumption forecasting [47], and more. Statistical-based time series prediction methods are commonly employed for linear time series modeling; however, real-world research reveals nonlinear characteristics within these time series.…”
Section: Introductionmentioning
confidence: 99%